Rethinking systemic change: economic evolution and institutions. Techn ical Paper - Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually so und definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of th e research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics, new institutional econom ics and complexity theory. There is a growing interest in these bodies of knowledge, combined often called New Economic Thinking, and how th ey affect economic development. Hence, while rethinking systemic chang e, this work also contributes to answering the broader question of how market systems approaches can contribute to inclusive economic develo pment. The answer, in short, is to shift the focus away from improving transactions at the micro level towards enabling actors to continuous ly shape an institutional landscape that supports inclusive economic e volution. This technical paper provides an in-depth review of the fiel ds of evolutionary economics, new institutional economics and complexi ty and social change. It is argued that economic development is a comp lex, non-linear and continuous evolutionary process. Both market and n on-market institutions matter greatly in shaping economic performance. The paper then explores the consequences of this understanding for ma rket development practice. It discusses how market development practit ioners can engage in and shape an intentional change processes. To tra nslate the theory into practice, seven principles are suggested that c an be applied to market systems development practice. The paper conclu des with a reframed look at systemic change in market systems developm ent. A discussion paper presents the key messages from the literature review and seven principles drawing from this literature, and a case s tudy offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transformi ng the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).